PORTOFOLIO (SEBAGAI KONSEP DASAR PERKEMBANGAN PENILAIAN BELAJAR SISWA) - Mayang Sari Lubis (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2018)
In the world of education often to find out the success or the success of student learning are determined from the results (values) have been obtained. So it's not uncommon to the existence of the presumption